Are Some Bribes More Harmful than Others? Exploring the Ethics Behind Anti-bribery Laws. (January 2014) - David-Barrett, Elizabeth
The proliferation of anti-bribery laws in recent years, particularly with the passage of the OECD Anti-Bribery Convention, sends a firm signal to companies that norms concerning corruption in international business have changed. With the increase in legal risk has come an increase in reputational risk. However, these laws and the cultures of enforcement around them, send conflicting messages about bribery being avoidable or indeed unethical. For example, many laws include an exemption or a defence for facilitation payments implying that such bribes are less unethical or that firms have a weaker responsibility to avoid paying them, than is the case for bribes 'to gain a business advantage'. This article seeks to analyse whether this distinction has a basis in ethics. It suggests that some bribes are less harmful than others in terms of their direct impact. However, all bribes are harmful, because they always undermine the rule of law. JEL: K2 Regulation and Business Law